The CMS experiment at the CERN LHC - Chatrchyan, S; Hmayakyan, G; Khachatryan, V; Sirunyan, A; Adam, W; Bauer, T; Bergauer, T; Bergauer, H; Dragicevic, M; Erö, J; Friedl, M; Frühwirth, R; et al. (Institute of Physics Publishing, 2008)
The Compact Muon Solenoid (CMS) detector is described. The detector operates at the Large Hadron Collider (LHC) at CERN. It was conceived to study proton-proton (and lead-lead) collisions at a centre-of-mass energy of 14 TeV (5.5 TeV nucleon-nucleon) and at luminosities up to 1034cm -2s-1 (1027cm-2s-1). At the core of the CMS detector sits a high-magnetic-field and large-bore superconducting solenoid surrounding an all-silicon pixel and strip tracker, a lead-tungstate scintillating-crystals electromagnetic calorimeter, and a brass-scintillator sampling hadron calorimeter. The iron yoke of the flux-return is instrumented with four stations of muon detectors covering most of the 4π solid angle. Forward sampling calorimeters extend the pseudo-rapidity coverage to high values (|n | ≤ 5) assuring very good hermeticity. The overall dimensions of the CMS detector are a length of 21.6 m, a diameter of 14.6 m and a total weight of 12500t. © 2008 IOP Publishing Ltd and SISSA.